2018
DOI: 10.4067/s0718-58392018000300447
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-induced plant volatiles emitted from avocado shoots infested by Oligonychus yothersi (Acari: Tetranychidae) increases the attraction of micro-coleopterans

Abstract: The avocado red mite, Oligonychus yothersi (McGregor) (Acari: Tetranychidae), is a polyphagous pest that causes damage to a wide range of plants. In Chile, is commonly found in avocado (Persea americana Mill.) orchards, and the plant damage is expressed as a reduction of photosynthetic activity in leaves, causing defoliation of trees under severe attack conditions. Oligota pygmaea (Solier) (Staphylinidae) and Parastethorus histrio (Chazeau) (Coccinellidae) microcoleopteran predators are found on 'Hass' avocado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The degree of infestation ( Figure 6) could also have contributed to different outcomes. The emission of HIPVs can qualitatively and quantitively vary depending on the population density of the insect feeding on host plants [72,73], with studies typically reporting a positive correlation between herbivore population density and VOC emission [74][75][76]. However, we only found a weak correlation between aphid infestation and VOC emission, and responding species and hybrids (except S. candida) were not heavily infested.…”
Section: Discussionmentioning
confidence: 46%
“…The degree of infestation ( Figure 6) could also have contributed to different outcomes. The emission of HIPVs can qualitatively and quantitively vary depending on the population density of the insect feeding on host plants [72,73], with studies typically reporting a positive correlation between herbivore population density and VOC emission [74][75][76]. However, we only found a weak correlation between aphid infestation and VOC emission, and responding species and hybrids (except S. candida) were not heavily infested.…”
Section: Discussionmentioning
confidence: 46%
“…Similarly, Shastani et al (2014) found that P. persimilis preferred synthetic MeSA at doses of 0.02-20 μg. However, P. histrio preferred MeSA concentration ranges 1-100 μg mL -1 , while O. pygmaea showed attraction at 1 and 10 μg mL -1 of synthetic MeSA (Rioja et al, 2018). Yet, when Shimoda (2010) offered synthetic MeSA (1 mg) vs. infested bean plants (P. vulgaris 'Nagauzuramame') with T. urticae, Neoseiulus californicus (Acari: Phytoseiidae) did not discriminate between these odor sources, showing that MeSA is an attractant for mite predators.…”
Section: Behavioral Responses Of Galendromus Occidentalismentioning
confidence: 91%
“…Our results reveal that G. occidentalis does not associate the HIPVs released by O. yothersi-infested avocado shoots (Table 4) with prey availability since they do not belong to the avocado system. In contrast, P. histrio and O. pygmaea are attracted to HIPVs emitted by O. yothersi-infested avocado shoots (Rioja et al, 2018). These predators use chemical cues from avocado-O.…”
Section: Behavioral Responses Of Galendromus Occidentalismentioning
confidence: 96%
See 2 more Smart Citations